Serum A20 level is associated with bone mineral density in male patients with type 2 diabetes mellitus - Han, Dongxu; Liu, Jingnan; Wang, Yu; Wang, Hongxia; Yuan, Lingdan; Jin, Wei; Song, Lige (Frontiers in Endocrinology, 2025)
BackgroundA20, also known as TNF-α-induced protein 3 (TNFAIP3), is a crucial negative regulator of inflammation and immune responses. Emerging evidence suggests that A20 is involved in the regulation of glucose metabolism and plays a significant role in bone metabolic diseases by inhibiting nuclear factor (NF)-κB activation. However, the potential relationship between serum A20 level and bone mineral density (BMD) in patients with type 2 diabetes mellitus (T2DM) has not been explored. This study aims to investigate the association between serum A20 level with BMD and bone turnover markers (BTMs) in patients with T2DM.MethodA total of 189 patients with T2DM and 183 non-diabetic individuals were included in the study based on the inclusion and exclusion criteria. Participants were categorized into normal BMD and low BMD groups. Baseline clinical histories were collected through face-to-face questionnaires. Participants underwent measurements of blood biochemistry and anthropometric, hand grip strength records and short physical performance battery (SPPB) assessment. Serum A20 level was quantified by enzyme-linked immunosorbent assay kit. Areal BMD was measured using dual-energy x-ray absorptiometry (DXA). A T-score of less than -1.0 at the lumbar spine 1-4, femoral neck and/or total hip was classified as low BMD.ResultsSerum A20 level was lower in patients with T2DM compared to controls [41.30 (29.91, 61.87) vs 76.01 (54.90, 109.64) pg/mL, P<0.001]. Bivariate correlation analysis revealed that A20 level was not associated with SPPB but negatively correlated with waist-to-hip ratio (WHR). Pearson correlation analysis showed A20 level was positively correlated with lumbar spine 1-4 BMD in male diabetic patients (r=0.253, P=0.032). Multivariate regression analysis showed a positive association between serum A20 level and lumbar spine 1-4 BMD (Beta=0.047; 95% CI: 0.007-0.086; P=0.024) after multivariate adjustment. Logistic regression analysis showed that lower serum A20 level predicted low BMD in male patients with T2DM (OR: 0.22; 95% CI: 0.09-0.59; P=0.002).ConclusionsType 2 diabetic patients exhibited lower serum A20 level compared to non-diabetic individuals. In male patients with T2DM, serum A20 level showed a significant positive correlation with lumbar spine 1-4 BMD and could serve as an independent negative predictor for low BMD.